Late Cretaceous (Maastrichtian) amphibians and squamates from northeastern Iberia. (January 2016) - Blanco, Alejandro; Bolet, Arnau; Blain, Hugues-Alexandre; Fondevilla, Víctor; Marmi, Josep
Abstract: Maastrichtian biodiversity of medium- and large-sized terrestrial vertebrates is well known in Europe and, specifically, in the Iberian Peninsula. Regarding small-sized herpetofaunas (lissamphibians and squamates), only a few European sites have yielded a significant amount of fossils, and they are still poorly known from the Iberian Peninsula. Recent fieldwork carried out at several sites exposing the Tremp Formation (Southern Pyrenees) has revealed four new localities yielding microvertebrates. Two of them (L'Espinau and Serrat del Rostiar-1) are relatively diverse in herpetofauna, containing albanerpetontids, four different anurans (two different alytids, a pelobatid or gobiatid and a palaeobatrachid), as well as six types of squamates (including scincomorphs, iguanids, anguids and probably gekkotans). Most of these groups are shared with other Campanian-Maastrichtian localities from eastern Iberia although, in some cases, morphological differences might suggest the presence of new lower-level taxa (i.e., genera or species). Also remarkable is the presence of alytines and likely gekkotans that would represent the oldest records of these taxa in Europe and in the Iberian Peninsula, respectively. Taxa of Laurasian origin are common at the Serrat del Rostiar-1 and L'Espinau localities, while Gondwanan taxa are lacking in all cases. Evidence for Asian immigrants (i.e., alytines) is found amongst anurans. Some differences regarding the faunal composition could be explained by environmental factors (i.e., coastal wetlands vs. fluvial settings), although the possibility of taphonomic biases cannot be ruled out. Highlights: Four new localities yielding microvertebrates remains are introduced. Assemblages are composed of Laurasian taxa, while Gondwanan taxa are absent. The oldest record for Alytinae and Gekkota in Europe are reported. Evidence for Asian immigrants during the Maastrichtian is found within anurans.